Aktualisasi Kepemimpinan Astha Brata Dalam Era Millenial - Imam Sutarjo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The teachings of astha brata leadership inherited from our ancestors are contained in old texts and are often presented in wayang shows, in this millennial era less and less known and unknown to the next generation of the nation's children. So it is very feared that the heritage of local wisdom values will be lost in the motherland. The purpose of this paper is to examine, express and actualize the concept of astha brata leadership in order to keep it alive, develop and be applied in the Unitary State of the Republic of Indonesia, on the basis of Pancasila, the 1945 Constitution and Bhinneka Tunggal Ika. In this study, a comparative approach is taken about Astha Brata's leadership through the Ramayana, Serat Ajipamasa, and the wayang story of Wahyu Makutharama. The method applied is content analysis, which includes the analysis of differences in content and personification in Astha Brata leadership. The results of the discussion, the task of a leader is to serve others, serve the people/people or others. The leadership of astha brata in the Ramayana was given/taught by Prabu Rama to Raden Bharata (his younger brother) and to Gunawan Wibisana (Ravana's younger brother); that a leader holds to 8 (astha = eight) brata (character / character, action) eight gods. In Serat Ajipamasa, the leadership of Astha Brata was taught by Prabu Ajipamasa (Kusumawicitra) to Sang Gandakusuma and Jayasusena, that a good leader adheres to the 8 (eight) contents of the world.